An Analysis of Australia Zoo’s Communication Strategies: The Irwins’ Involvement - Raissa Almira (Journal of World Science, 2024)
Australia Zoo, a privately owned establishment in Beerwah, Queensland, Australia, initially founded in 1970 as the 'Beerwah Reptile Park' by the family of Steve Irwin, a renowned Australian Wildlife Conservationist, serves as the focus of this research. The study aims to explore the communication strategies employed by Australia Zoo from 2020 to 2023. The primary objective is to examine these strategies with a particular emphasis on the involvement of The Irwins family. This research utilizes analysis and evaluation methods to identify the communication tactics implemented by the zoo, assess the impact and effectiveness of The Irwins' participation, and appraise the utilization of The Irwins family branding in attracting and retaining visitors. The research findings reveal the significant role of The Irwins family in enhancing the zoo's public image and visitor engagement. The study also highlights the effectiveness of various communication strategies in reinforcing Australia Zoo's unique identity. The outcomes of this evaluation furnish recommendations to enhance future communication strategies, thereby reinforcing Australia Zoo's image and allure as a distinctive tourist destination influenced by the enduring legacy of Steve Irwin and his family. These implications underscore the importance of strategic communication in maintaining and growing a wildlife conservation establishment's public profile and visitor base.